Modelling of specific energy requirements in machining as a function of tool and lubricoolant usage. Issue 1 (2016) - Priarone, Paolo C.; Robiglio, Matteo; Settineri, Luca; Tebaldo, Vincenzo
Abstract: Energy consumption is a key player in material removal processes. Models for estimating the specific energy consumption or for computing the total direct energy requirements have been developed to date. This paper proposes a comprehensive model for the system-level energy analysis of machining processes, which includes all the activities related to workpiece material production, material removal, tool and cutting fluid production and usage. The application of the model to the turning of a Ti–6Al–4V alloy (under wet, MQL, and dry cutting conditions) is discussed. The results allow the identification of the optimum process parameters for energy footprint minimization.